Periodontal disease reduces water and sodium intake induced by injection of muscimol into the lateral parabrachial nucleus - de Melo e Silva, Talita; Bearare, Gabriela P.; Sumida, Doris Hissako [UNESP]; Callera, João Carlos [UNESP] (Elsevier, 2013)
Objective: Gamma-aminobutyric acid A (GABAA) receptor activation with muscimol in the lateral parabrachial nucleus (LPBN) induces water and 0.3 M NaCl intake. The purpose of this study was to investigate whether a local inflammatory event, such as periodontal disease (PD), is able to alter the effects of muscimol on water and 0.3 M NaCl intake in fluid-replete rats and in rats treated with furosemide (FURO) combined with captopril (CAP) injected subcutaneously. Design: Male Wistar rats were divided into two groups: with PD and those without PD (control condition). Fifteen days after PD, both groups had cannulas implanted bilaterally into the LPBN. Results: In fluid-replete rats without PD, injections of muscimol (0.5 nmol/0.2 μl) into the LPBN induced 0.3 M NaCl and water intake and a pressor response. In fluid-replete rats with PD, a decrease was observed in water intake and pressor response but not in 0.3 M NaCl intake. In control rats with FURO + CAP treatment, injections of muscimol into the LPBN increased 0.3 M NaCl and water intake. In PD rats with FURO + CAP treatment, a decrease was observed in 0.3 M NaCl and water intake after muscimol in the LPBN. Alveolar bone loss and interleukin-6 (IL-6) and tumour necrosis factor-α (TNF-α) plasmatic concentration were higher in PD rats in comparison with controls. Conclusion: These results suggest that PD is able to reduce the pressor response and the dipsogenic and natriorexigenic effects induced by the activation of GABAA receptors in the LPBN, probably due to the elevation of the plasmatic concentration of pro-inflammatory cytokines IL-6 and TNF-α. © 2013 Elsevier Ltd. All rights reserved.
Keywords: GABA receptors; Lateral parabrachial nucleus; Muscimol; Periodontal disease; Sodium appetite; Thirst